2007
DOI: 10.1007/s00383-007-2067-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum alpha-fetoprotein in Wilms tumor may follow the same pattern of other fetal neoplasms after treatment: evidence from three cases

Abstract: Alpha-fetoprotein (AFP) is a common tumoral marker in pediatric neoplasms; increased serum levels are usually encountered in tumors arising from tissues producing AFP during fetal life. However, elevation of such protein is rarely found in patients with Wilms tumor (WT). Three patients with WT and elevated serum AFP were studied over the course of the disease. One patient had left WT with invasion of aorto-caval lymph nodes and lung metastases. The second patient was referred to our center for abdominal recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In our case, the tumor showed dimensional regression after preoperative chemotherapy and the elevation of AFP middle responded to chemotherapy and returned to normal after nephrectomy. AFP levels have been reported to be higher in patients with metastatic disease, than in one case with thrombosis in inferior vena cava [1,12]. This case also had an associated testicular swelling, which in fact was the reason for investigating the AFP levels.…”
Section: Afp Levelsmentioning
confidence: 79%
See 1 more Smart Citation
“…In our case, the tumor showed dimensional regression after preoperative chemotherapy and the elevation of AFP middle responded to chemotherapy and returned to normal after nephrectomy. AFP levels have been reported to be higher in patients with metastatic disease, than in one case with thrombosis in inferior vena cava [1,12]. This case also had an associated testicular swelling, which in fact was the reason for investigating the AFP levels.…”
Section: Afp Levelsmentioning
confidence: 79%
“…There are only few reports describing raised AFP in classic Wilms' tumor [1,8,9,11,12] [1,8,9,11,12]. Kısmet et al [8] suggested that persistence of high AFP level during preoperative chemotherapy period could reflect a poor response to chemotherapy.…”
Section: Afp Levelsmentioning
confidence: 99%
“…For example, Roth and colleagues first described WT presenting with elevated serum AFP [38]. Since this initial description, only four other WT cases have been documented with histologically classic type WT and elevated AFP [39][40][41]. More notably, elevated AFP is seen in the teratoid WT, in which more than 50% of the tumor is composed of teratoid elements [42].…”
Section: Afp and Associated Rare Pediatric Solid Cancersmentioning
confidence: 99%
“…Alpha-fetoprotein (AFP) is an oncodevelopmental antigen that is commonly elevated in patients with hepatoblastoma and yolk salk tumor. High serum AFP levels are rarely found in patients with WT and few cases were reported [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%